CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCES FOR MINING COMPANIES OF MONGOLIA - Д.Баттуяа,; Д.Лхагвасүрэн,; Г.Алтанзаяа, (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
In recent years, there are increased empirical studies on the relationship between Corporate Financial Performance (CFP) and Corporate Social Performance (CSP). More academics perceive that the social responsibility of a business is to increase its profits. Based on the view many papers focus that how CSR has effects on CFP. The previous literatures with the relation between CSR and CFP show different results that are made in the different financial measures and different countries. There are not enough for study in case of Mongolia. Thus, the paper examines the relationship between CSR and CFP. Our study has covered 5 years’ period during 2013 to 2017 for 6 mining companies listed on the MSE. The data is collected from database of Ministry of Finance Mongolia, Mongolia Stock Exchange and report for The Extractive Industries Transparency Initiative (EITI). In this research, financial performance measures are ROA as accounting based measure and Tobin’s Q as market based measure as used in the previous studies. Employee and public responsibility are significant positive impact on Tobin’s Q. The result reports no significant relationship between environmental responsibility and CFP for mining companies. This suggests that CSR including environmental responsibility could not significantly influence on the profit and market value of companies. The future study relies on the different relationships between CSR and CFP.